Penggunaan Jasa Kurir Dalam Jual Beli Online Tinjauan Kompilasi Hukum Ekonomi Syariah - Winda, Winda (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
An agreement can be understood that an agreement is an agreed action to be carried out by someone with someone, several people with several other people (one party with another party). In law, if an act results in the law, the act is called a legal act, where legal actions are agreements entered into by the parties. Default is a bad performance or breach of contract which means that the obligations are not carried out properly as imposed by the contract. The above problems will be answered by the author by conducting field research, the data sources of this research are primary data and secondary data. Data collection techniques using field studies, namely interviews and documentation. Interviews were conducted with Service Users who perform courier services in delivering goods (packages) in Kampung Mesjid Village, Kualuh Hilir District, Labuhan Batu Utara Regency. This data processing technique is after the data is complete and collected. Based on the results of this study, it shows that the use of courier services in online buying and selling in Kampung Mesjid Village, Kualuh Hilir District, Labuhan Batu Utara Regency, couriers have broken promises in delivering goods. The review of the Compilation of Sharia Economic Law on the Use of Courier Services in Online Buying and Selling who does not break promises is contained in article 36 regarding breaking promises: Not doing what he promised to do. Carry out what was promised, but not as promised. Doing what was promised but late, or doing something that according to the agreement should not be done.